Participatory environmental assessment with teenagers from a municipal ecological reserve from the design of a proposed non-formal environmental education - García-Gil, Gerardo; Aguilar Cordero, Wilian de Jesús; Vermont Ricalde, Rita Minelia; Peña, Yolanda Oliva (Acta Universitaria, 2020)
Social participation in the management of natural protected areas (NPA) is a fundamental aspect for the proper functioning of the land intended for the conservation of natural resources. Equally important is to involve younger generations; therefore, a participatory environmental assessment was held with a group of 16 teenagers from Dzoyaxche, Merida, Yucatan, located in the Cuxtal Ecological Reserve. The study was integrated by four methodological phases and one cross-cutting theme, which raised the socioenvironmental problems of the community: 17 main problems integrated in eight main themes. The results were used to design an Intercultural Plan of Non-Formal Environmental Education for teenagers from the Cuxtal Ecological Reserve. The plan was comprised by six action lines: 1) Education and training; 2) Production of intercultural didactic materials; 3) Projects Generation; 4) Research; 5) Monitoring and evaluation; 6) Coordination of efforts. The plan was accepted by the young participants, since they felt involved in the whole process and were motivated to implement it in their community at the Reserve.